Fe-Binding Dissolved Organic Ligands in the Oxic and Suboxic Waters of the Black Sea - Loes J. A. Gerringa; Micha J. A. Rijkenberg; Johann Bown; Andrew R. Margolin; Patrick Laan; Hein J. W. de Baar (Frontiers in Marine Science, 2016)

Natural enemies from South Africa for biological control of Lagarosiphon major (Ridl.) Moss ex Wager (Hydrocharitaceae) in Europe - J.-R. Baars; J. A. Coetzee; G. Martin; M. P. Hill; J. M. Caffrey (Hydrobiologia, 2010)

Campylobacter jejuni bacteremia and Helicobacter pylori in a patient with X-linked agammaglobulinemia - T. van den Bruele; P. E. C. Mourad-Baars; E. C. J. Claas; R. N. van der Plas; E. J. Kuijper; R. G. M. Bredius (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Can photoinhibition control phytoplankton abundance in deeply mixed water columns of the Southern Ocean? - Anne-Carlijn Alderkamp; Hein J. W. de Baar; Ronald J. W. Visser; Kevin R. Arrigo (Limnology and Oceanography, 2010)
To study how natural Southern Ocean phytoplankton communities acclimate to rapid fluctuations in irradiance levels that result from deep wind‐driven mixing of the upper water column, we measured their fluorescence properties (F v :F m , maximum quantum yield of photosystem II; and qN , non‐photochemical quenching) and pigment composition. Values of F v :F m were low (> 0.46) and qN was high ( v :F m and recovery was slow under subsequent incubation at low irradiance. This suggests that phytoplankton cells are frequently photodamaged when mixed up to the surface from depth. Recovery of F v :F m was suppressed when lincomycin was added, inhibiting synthesis of the photosystem II reaction center D1 protein. This indicates that D1 protein repair is crucial in maintaining photosynthetic performance under fluctuating irradiance levels. Regions within the Antarctic Circumpolar Current (ACC) with a deep UML had lower depth‐integrated phytoplankton biomass than regions close to the Antarctic continent with a shallow UML. Surprisingly, the depth‐averaged light level within the UML in these latter regions was lower than in the ACC. Thus, it appears that photodamage incurred during the high irradiance portion of the vertical mixing cycle, rather than light limitation, controls phytoplankton growth in regions of the Southern Ocean with a deep UML. This concept represents a shift from the widely accepted paradigm that phytoplankton growth in the open Southern Ocean is limited by low levels of light or inadequate iron supply.

Comparison of macroinvertebrate community structure and driving environmental factors in natural and wastewater treatment ponds - G. Becerra Jurado; M. Callanan; M. Gioria; J.-R. Baars; R. Harrington; M. Kelly-Quinn (Hydrobiologia, 2009)

In situ and remote-sensed chlorophyll fluorescence as indicator of the physiological state of phytoplankton near the Isles Kerguelen (Southern Ocean) - Klaas R. Timmermans; Hendrik J. van der Woerd; Marcel R. Wernand; Merijn Sligting; Julia Uitz; Hein J. W. de Baar (Polar Biology, 2008)

Biology and host range of Aconophora compressa, a candidate considered as a biocontrol agent of Lantana camara in Africa - F. Heystek; J. -R. Baars (BioControl, 2005)

Growth rates, half‐saturation constants, and silicate, nitrate, and phosphate depletion in relation to iron availability of four large, open‐ocean diatoms from the Southern Ocean - Klaas R. Timmermans; Bas van der Wagt; Hein J. W. de Baar (Limnology and Oceanography, 2004)
Four large, open‐ocean diatoms from the Southern Ocean ( Actinocyclus sp., Thalassiosira sp., Fragilariopsis kerguelensis , and Corethron pennatum ) were grown in natural (low iron) Southern ocean seawater with increasing Fe concentrations. With increasing dissolved iron (Fe diss ) concentrations, the growth rates increased three‐ to sixfold. The species with the smallest cells had the highest growth rates. The half‐saturation constants (Km) for growth were low (0.19−1.14 nmol L −1 Fe diss ), and close to the ambient Fe diss concentrations of 0.2 nmol L −1 . The range in K m with respect to Fe diss also varied with the size of the diatoms: the smallest species had the lowest K m and the largest species had the highest K m . As Fe diss concentrations decreased, silicate consumption per cell increased, but nitrate consumption per cell decreased. Phosphate consumption per cell varied without clear relation to the dissolved iron concentrations. The differences in nutrient consumption per cell resulted in marked differences in elemental depletion ratios in relation to Fe diss concentrations, with the depletion ratios being most affected by iron limitation in the largest cells. These experimental findings are in agreement with previous laboratory and field studies, showing the relatively high requirements of large diatoms for Fe. The size‐dependent response of the diatoms with respect to nutrient depletion is a good illustration of the effects of Fe on silicate, nitrate, and phosphate metabolism.

Geographical range and impact of five biocontrol agents established on Lantana camara in South Africa - J-R. Baars; F. Heystek (BioControl, 2003)

Zinc‐bicarbonate colimitation of Emiliania huxleyi - Erik T. Buitenhuis; Klaas R. Timmermans; Hein J. W. de Baar (Limnology and Oceanography, 2003)
In analogy to the Fe hypothesis, the Zn hypothesis states that Zn may limit primary production in some regions of the world oceans and therefore influence the global carbon cycle. The proposed mechanism is via carbon limitation due to a lack of the cofactor Zn in carbonic anhydrase. In the current conceptual model for the use of inorganic carbon by E. huxleyi , carbonic anhydrase in the chloroplast generates CO 2 from HCO 3 − at the site where CO 2 is fixed by ribulose bisphosphate carboxylase oxygenase (Rubisco). The H + that is required in this reaction comes from calcification. From this it can be expected that carbonic anhydrase affects the use of HCO 3 − in photo‐synthesis. First, we grew E. huxleyi under Zn 2+ limitation. The K 1/2 for growth of E. huxleyi is 19 ± 8 pmol L −1 Zn 2+ with a minimum requirement of 9 ± 3 pmol L −1 . Additions of both ethylenediaminetetraacetic acid (EDTA) and ZnCl 2 show that EDTA is not detrimental to E. huxleyi up to a concentration of 200 µmol L −1 . Then we grew E. huxleyi under Zn 2+ ‐HCO 3 − colimitation to test the conceptual model outlined above. The results were partly inconsistent with the model. Contrary to what was expected from the conceptual model, the efficiency of CO 2 use decreased when both Zn 2+ and HCO 3 − concentrations were low, even though the experiment was conducted at a constant high concentration of CO 2 . This shows that Zn 2+ , and possibly carbonic anhydrase activity, are needed for CO 2 fixation also. In accordance with the model, we found that Zn 2+ affects the efficiency of HCO 3 − use by E. huxleyi . Since the lowest Zn 2+ concentration in the Northeast Pacific is ~0.4 pmol L −1 , Zn limitation of E. huxleyi growth may indeed occur.

Not all eukaryotic algae can replace zinc with cobalt: Chaetoceros calcitrans (Bacillariophyceae) versus Emiliania huxleyi (Prymnesiophyceae) - Klaas R. Timmermans; Josje Snoek; Loes J. A. Gerringa; Ingrid Zondervan; Hein J. W. de Baar (Limnology and Oceanography, 2001)
Zinc and cobalt are essential trace metals for phytoplankton growth and can substitute for each other metabolically in some eukaryotic algal species, especially in some marine diatoms and coccolithophorids. In the present study, it is reported that in the marine diatom Chaetoceros calcitrans , Co cannot replace Zn: in contrast, Co substitution of Zn was found in Emiliania huxleyi . It is concluded that Co can substitute for Zn but that the phenomenon is species/genera‐specific. Differing ability to substitute Zn with Co can be regarded as an additional factor affecting phytoplankton biomass and/ or species composition.

Growth rates of large and small Southern Ocean diatoms in relation to availability o iron in natural seawater - Klaas R. Timmermans; Loes J. A. Gerringa; Hein J. W. de Baar; Bas van der Wagt; Marcel J. W. Veldhuis; Jeroen T. M. de Jong; Peter L. Croot; Marie Boye (Limnology and Oceanography, 2001)
Blooms of large diatoms dominate the CO 2 drawdown and silicon cycle of the Southern Ocean in both the past and present. The growth of these Antarctic diatoms is limited by availability of iron (and light). Here we report the first assessment of growth rates in relation to iron availability of two truly oceanic Antarctic diatom species, the large, chain‐forming diatom Chaetoceros dichaeta and the small, unicellular diatom C. brevis . In Filtered natural, untreated Southern Ocean water, a maximum specific growth rate of 0.62 ± 0.09 d −1 and a Km for growth of 1.12 x 10 9 M dissolved iron was calculated for C. dichaeta . This response could only be seen during a long‐day light period. C. brevis maintained growth rates of 0.39 ± 0.09 d −1 with and without iron addition, even under short‐day light conditions, and could only be forced into iron limitation by adding the siderophore desferri‐ferrioxamine B (DFB), an iron immobilizing agent. Using this approach, the low Km value for growth of 0.59 × 10 −12 M dissolved Fe was calculated for this species. The size‐class dependent growth response to iron (and light) confirms the key role of these parameters in structuring Southern Ocean ecosystems and thus the CO 2 dynamics and the silicon cycle.